The Role of the Young Generation as the Foundation for the Sustainability of the National Halal Industry - Febiola Anggun Tri Setyo; Junnaidi, Junnaidi; Wildan Romdhoni; Hawa Gazani; Muhammad Ersya Faraby (Al-Abqori: Journal of Islamic Thought Studies, 2025)
The halal industry in Indonesia continues to show rapid growth, supported by the world's largest Muslim population and increasing awareness of halal products. By 2025, the Indonesian halal market will have thousands of companies in the food, beverage, and pharmaceutical sectors with thousands of halal-certified products, indicating high demand and industry compliance. The government, through various policies and programs, actively encourages the development of this industry, including halal certification, training, and cross-sector collaboration. With increasing investment and the support of technology and the younger generation as drivers of innovation, Indonesia is optimistic that it will become a competitive global center for the halal industry. The growth of the halal industry is expected to be the main driver of inclusive and sustainable national economic development in the future.